Rapid Induction of Mesenchymal Stem Cells to Neural Cells (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background:-Human umbilical cord blood- mesenchymal stem cells(HUCB-MSCs) hold great promise invitro neural differentiation and therapy for neurodegenerative disorders. It has demonstrated that the numberand differentiating potential of bone marrow mesenchymal stem cells (MSCs) decrease with age. Therefore,the search for alternative sources of MSCs is of significant value.Objective:-To determine the possibility of obtaining clonally expanded UCB-MSCs and evaluate their rapidinduction and differentiation into neural cells in vitro.Methods:-MSCs were isolated from HUCB by combining gradient density centrifugation with plasticadherence. In order to identify factors that able to lead to neural differentiation, the cultured cells weretreated with retinoic acid (RA) and B-mercaptoethanol (BME). Differentiating characterization of UCBMSCswere detected by immunocytochemistry analysis.Results:-UCB-MSCs appeared like the fibroblast cell and these cells were extensively expanded in culture.The results showed that UCB-MSCs were positive for CD71and CD90 but were negative for CD34. Theimmunocytochemistry staining indicated that the differentiated cells give positive response for nestinemarker. The result confirmed for neural progenitor differentiation of MSCs.Conclusion: The results of this study confirmed that UCB provides a great source of stem cells for using intreatment of neurodegenerative disorders of the central nervous system.
Keywords: mesenchymal stem cells, umbilical cord blood, neuronal induction, in vitro.